Serbia, the Serbo-Albanian conflict and the First Balkan War - Bataković Dušan T. (Balcanica, 2014)
After the restoration of Serbia in 1830, the areas of medieval Serbia left out of her borders were dubbed Old Serbia - Kosovo, Metohija, Rascia (the former sanjak of Novi Pazar and the neighbouring areas). Old Serbia (from 1877 onwards the vilayet of Kosovo) was dominated by local Albanian pashas, whereas the Christian Orthodox Serbs and their villages were attacked and pillaged by Muslim Albanian brigands. The religious antagonism between Muslims and Christians expanded into national conflict after the 1878 Albanian League had claimed the entire “Old Serbia for Greater Albania”. The position of Christian Orthodox Serbs, who accounted for a half of the population at the end of the nineteenth century, was dramatically aggravated due to Muslim Albanians' tribal anarchy, Austria-Hungary's pro-Albanian agitation and, after 1908, frequent Albanian rebellions. All efforts of Serbia to reach a peaceful agreement with Muslim Albanian leaders in Old Serbia before the First Balkan War had ended in failure. The First Balkan War was the most popular war in Serbia’s history as it was seen as avenging the 1389 Battle of Kosovo which had sealed the Ottoman penetration into the Serbian lands. In October 1912, Serbia liberated most of Old Serbia, while Montenegro took possesion of half of the Rascia area and the whole of Metohija. While the decimated and discriminated Serb population greeted the Serbian and Montenegrin troops as liberators, most Albanians, who had sided with the Ottomans, saw the establishment of Serbian rule as occupation.